APPLICATION OF THE COOPERATIVE LEARNING TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) LEARNING MODEL TO IMPROVE IPS LEARNING OUTCOMES CLASS IV STUDENTS OF SDN 006 SENCANO JAYA - Yusrizal (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
The problem in this research is the low social studies learning outcomes. The purpose of this study was to improve the social studies learning outcomes of the fourth grade students of SDN 006 Sencano Jaya, by applying the Student Teams Achievement Division (STAD) type of cooperative learning model. The hypothesis in this study is that if the cooperative learning model (STAD) is applied, it can improve the social studies learning outcomes of students of SDN 006 Sencano Jaya class. The results showed that the teacher activity in the first cycle of the first meeting showed an average of 70.83%, in the first cycle of the second meeting an average of 83.33%. In the second cycle, the first meeting was 87.50%, in the second cycle the second meeting had an average of 95.83%. Teacher activity in this study increased. Student activity in the first cycle of the first meeting with an average of 58.33% in the first cycle of the second meeting was 70.83%, in the second cycle of the first meeting an average of 75.00% in the second cycle of the second meeting with an average of 91.66%. Student activity in this study also increased. The initial data of social studies learning results showed that only 11 students completed with a percentage of 40.74% who did not complete 16 people or 59.25% of students who obtained a basic score above the minimum completeness criteria standard (KKM). In the UH I who completed 15 people or the percentage of 55.55% who did not complete 12 people with a percentage of 44.41%. At UH II, 24 people or 88.88% who did not complete were only 3 students or with a percentage of 11.11%. Social studies learning outcomes in this study are increasing, so with the application of the Cooperative learning model type Students Teams Achievement Division (STAD).